P01.034 Prospective evaluation of alternative therapies in glioma patients in France. (19th September 2018) - Le Rhun, E; Lebrun Frenay, C; Devos, P; Darlix, A; Lorgis, V; Ahle, G; Boone, M; Taillandier, L; Curtit, E; Gras, L; Bourg, V; Ramirez, C; et al.
Abstract: Background: The main objective of this study was to explore the patterns of alternative therapy use, in parallel to the standard treatment, in glioma patients in France. Material and Methods: Questionnaires were distributed during visits at hospital and filled in and returned anonymously by adult patients with histologically confirmed glioma and with an ECOG performance score of 0–2. The protocol was approved by the French authorities on April 13th, 2016. Descriptive analyses of the population as well as correlation analysis according to gender, age, WHO grade IV versus other, recurrent disease as declared by the patients versus none, were conducted. Results: Two hundred questionnaires were collected. Patients were male in 65% of the cases. Median age was 46 (range 18–85). Forty-six patients had glioblastoma, 83 patients declared having recurrent disease. Patients declared taking a complementary treatment in 46.5% (mainly vitamins and other food supplements), having modified their diet (ketogenic diet, Servent-Schreiber diet, addition of curcuma) in 48%, and using another alternative medicine approach (mainly magnetism, acupuncture, sophrology), in 34%. In total, 69% of the patients declared using at least one of these approaches. No difference was observed according to gender, age or occurrence of a recurrence, however, glioblastoma patients used significantly more often at least one approach (p<0.0001). Information on these interventions were mainly derived from relatives or media. Cost was 200 euros per month or more in 25% for complementary treatment, in 20% for diet and in 5% for alternative medicine. These approaches were mainly considered as good for quality of life and experienced as efficient. Conclusion: Alternative therapies are frequently used by patients and should be discussed with patients and caregivers during the course of the disease to identify patient needs and preferences as well as potential interactions with tumor-specific treatments.